On the Propagation Path of Magma‐Filled Dikes and Hydrofractures: The Competition Between External Stress, Internal Pressure, and Crack Length. (25th April 2019) - Maccaferri, F.; Smittarello, D.; Pinel, V.; Cayol, V.
Abstract: Mixed‐mode fluid‐filled cracks represent a common means of fluid transport within the Earth's crust. They often show complex propagation paths which may be due to interaction with crustal heterogeneities or heterogeneous crustal stress. Previous experimental and numerical studies focus on the interplay between fluid overpressure and external stress but neglect the effect of other crack parameters. In this study, we address the role of crack length on the propagation paths in the presence of an external heterogeneous stress field. We make use of numerical simulations of magmatic dike and hydrofracture propagation, carried out using a two‐dimensional boundary element model, and analogue experiments of air‐filled crack propagation into a transparent gelatin block. We use a 3‐D finite element model to compute the stress field acting within the gelatin block and perform a quantitative comparison between 2‐D numerical simulations and experiments. We show that, given the same ratio between external stress and fluid pressure, longer fluid‐filled cracks are less sensitive to the background stress, and we quantify this effect on fluid‐filled crack paths. Combining the magnitude of the external stress, the fluid pressure, and the crack length, we define a new parameter, which characterizes two end member scenarios for the propagation path of a fluid‐filled fracture. Our results have important implications for volcanological studies which aim to address the problem of complex trajectories of magmatic dikes (i.e., to forecast scenarios of new vents opening at volcanoes) but also have implications for studies that address the growth and propagation of natural and induced hydrofractures. Plain Language Summary: Fluids move within the Earth by means of different mechanisms. One of the most relevant mechanisms, particularly for magma transport within the lithosphere, is the propagation through fluid‐filled fractures: the fluid (or magma) can create its own path through the crustal rocks by fracturing them. If the density of the fluid is lower than the density of the rocks, the fluid would be pushed upward by buoyancy (similarly to a gas bubble in water). However, the propagation path followed by these fluid‐filled fractures may be complex. This may be due to several factors, including the forces (stresses) acting within the crust because of plate tectonic or because of remarkable topographic features. Here we make use of computer simulations and laboratory experiments to test how fluid‐filled fractures interact with such crustal stresses. We quantify how the competition between (i) crustal stresses, (ii) fluid (or magma) pressure, and (iii) the length of a fluid‐filled fracture may affect its direction of propagation. We define a critical range of values for a parameter which may help identifying the path of a fluid‐filled fracture propagating through the Earth crust. Our results may have important implications for volcanological studies which aim to forecast scenarios of new eruption locations. Key Points: We make use of analogue experiments and numerical simulations to study the propagation path of fluid‐filled cracks in interaction with crustal stresses We show and quantify how the competition between crustal stresses, fluid pressure, and crack length affect the path of fluid‐filled cracks We provide a critical range of values for a parameter which may help predicting the propagation path of a fluid‐filled crack